How can China Become a Real Insurance Power? - Findings from the study on the impacts of social advance on insurance market - Feng, Liyu (Advances in Social Sciences Research Journal, 2017)
Social advance is the process in which elements constituting society develop and change. As insurance is a social product and serve for the whole society, we want to know whether or not and how social development exert influence on insurance sector. In this study, we use data of 48 economies in period of 2001-2015 to explore the impacts of social advance on insurance market by setting panel and cross-section models from demographic, economic, medical and institutional aspects. The measures of insurance market are insurance penetration and insurance density. The results show that financial depth, social security and political stability appear to have no robust association with insurance sector, while certify the impacts of demographic, medical and other economic factors on the insurance measures, especially on insurance density. Meanwhile, there are marked differences between the results from developing economies and those from the full sample. As China is a “big insurance market” with insufficient coverage and depth, we can draw some useful things from the analysis and promote the transformation of China insurance market from a big one to a real power.